2020
DOI: 10.3390/polym12010089
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization of Propylene with Higher α-Olefins by a Pyridylamidohafnium Catalyst: An Effective Approach to Polypropylene-Based Elastomer

Abstract: In this contribution, we explored the copolymerization of propylene with higher α-olefins, including 1-octene (C8) 1-dodecene (C12), 1-hexadecene (C16) and 1-eicosene (C20), by using a dimethyl pyridylamidohafnium catalyst. A series of copolymers with varied comonomer incorporation, high molecular weight and narrow molecular weight distribution were obtained at mild conditions. The effects of the insertion of the comonomers on the microstructure, thermal and final mechanical properties were systemically studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…In this study, therefore, we would like to conduct RM simulations of the 1-octene polymerization reaction catalyzed by the (pyridylamido)­Hf­(IV) complex, which is used for industrial-scale production of various polyolefins, aiming for its future application to more complex chemical reaction like chain-shuttling polymerization catalyst system, , where ethylene/1-octene block copolymers are produced. We would like to focus on the most important properties that have been paid attention to, i.e., activities and the living characters of catalytic systems, which determine the molecular weight distribution (MWD) of the polymers. It is reported that the 1-octene polymerization by the (pyridylamido)­Hf­(IV) catalyst proceeds about twice faster with B­(C 6 F 5 ) 4 – than with MeB­(C 6 F 5 ) 3 – , which means that the activity of the catalyst is higher with B­(C 6 F 5 ) 4 – than with MeB­(C 6 F 5 ) 3 – . Notably, not only the catalytic activity but also the living character of the catalytic system is dependent on the CAs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, therefore, we would like to conduct RM simulations of the 1-octene polymerization reaction catalyzed by the (pyridylamido)­Hf­(IV) complex, which is used for industrial-scale production of various polyolefins, aiming for its future application to more complex chemical reaction like chain-shuttling polymerization catalyst system, , where ethylene/1-octene block copolymers are produced. We would like to focus on the most important properties that have been paid attention to, i.e., activities and the living characters of catalytic systems, which determine the molecular weight distribution (MWD) of the polymers. It is reported that the 1-octene polymerization by the (pyridylamido)­Hf­(IV) catalyst proceeds about twice faster with B­(C 6 F 5 ) 4 – than with MeB­(C 6 F 5 ) 3 – , which means that the activity of the catalyst is higher with B­(C 6 F 5 ) 4 – than with MeB­(C 6 F 5 ) 3 – . Notably, not only the catalytic activity but also the living character of the catalytic system is dependent on the CAs.…”
Section: Introductionmentioning
confidence: 99%
“…Polyolefins are manufactured by cracking the petrochemical sources such as crude oil and natural gas [5,6]. Polyethylene (PE) polymers including low-density polyethylene (LDPE) and high-density polyethylene (HDPE) are the most famous polyolefins commonly employed in the food packaging industry, since they are easily heat sealable, can be fabricated into rigid films, with a good barrier against moisture and water vapor [7,8]. In spite of such features, their poor surface properties, including adhesion, wettability, and cytocompatibility, impede their integration with other materials to form multi-layered laminates.…”
Section: Introductionmentioning
confidence: 99%
“…This catalyst has recently been utilized in a new polymerization technology, chain shuttling polymerization (CSP), where ethylene/1-octene multiblock copolymers can be obtained by introducing a chain transfer agent into a solution mixture of two catalyst species with different 1-octene incorporation abilities. Hence, a lot of mechanistic studies and ligand modifications of (pyridylamido)­Hf­(IV) catalyst have been conducted so far.…”
Section: Introductionmentioning
confidence: 99%